Pengaruh Live Streaming, Online Customer Review dan Price Discount terhadap Purchase Intention pada Brand YSL Beauty Indonesia di Platform Tiktok - Revalina Talitha Yasri; Dita Puruwita; Ivan Putranto (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to examine and analyze the influence of Live Streaming, Online Customer Review, and Price Discount on Purchase Intention toward YSL Beauty Indonesia products on the TikTok platform. This study employed a quantitative research method using a questionnaire as the data collection instrument. The population consisted of YSL Beauty Indonesia consumers residing in the Greater Jakarta area (Jabodetabek). The sampling technique used was non-probability sampling with a purposive sampling method, resulting in a total of 200 respondents. The data were analyzed using multiple linear regression analysis, supported by descriptive statistical analysis, instrument testing, classical assumption tests, hypothesis testing (t-test and F-test), and the coefficient of determination (R²), with the assistance of IBM SPSS Statistics version 29.. The results indicate that Live Streaming, Online Customer Review, and Price Discount each have a positive and significant effect on Purchase Intention. Furthermore, these three variables simultaneously have a positive and significant effect on Purchase Intention, with Price Discount identified as the most influential variable. Therefore, optimizing live streaming activities, managing online customer reviews, and offering attractive price discounts can serve as effective digital marketing strategies to increase consumers' purchase intention toward YSL Beauty Indonesia products on the TikTok platform.